Internet routing registries, data governance, and security. Issue 1 (2nd January 2017) - Kuerbis, Brenden; Mueller, Milton
ABSTRACT: Routing is fundamental to the workings of the internet, yet the basic routing protocol, Border Gateway Protocol (BGP), is known to be insecure. This paper uses institutional economics to examine internet routing registries, which are used by network operators to mitigate the security flaws in BGP. Secure routing of internet traffic is characterised as a problem in the distributed governance of data. The highly distributed and decentralised exchange of routing announcements and routing policy data among network operators affords many opportunities for error or manipulation. This paper considers various solutions to the data governance problems associated with routing, in light of actors' incentives and collective action problems. We compare IRRs to other methods of governing routing data in a way that enhances internet security, such as Resource Public Key Infrastructure and Border Gateway Protocol Security, Mutually Agreed Norms on Routing Security, and a blockchain supported routing registry.